Analisis Efisiensi Bank Persero dan Bank Asing dengan Metode Stochastic Frontier Analysis (SFA) dan Analysis Of Variance (ANOVA) (Studi Kasus pada Bank Persero dan Bank Asing di Indonesia periode tahun 2010-2014) - Putri, Asti Mardiana; Mawardi, Wisnu (Faculty of Economics and Business Diponegoro University, 2016)
The dominant role of banks in Indonesia makes bank should have a healthy financial performance. A way to maintain good financial performance by analyzing the level of efficiency so it can be seen how banks are efficient, healthy and able to survive in any economic conditions. The purpose of this research is to analyze the efficiency level of state-owned banks and foreign banks in Indonesia in period between 2010-2014 based on three approaches; operational approach, intermediation approach and asset approach. The analytical method used are Stochastic Frontier Analysis (SFA) using production function and Analysis Of Variance (ANOVA). SFA method used to measure efficiency level and the result appears in numeric score 0-1 form. The closer the result with score 1 so the banks getting closer with the perfect efficiency level. One Way ANOVA is used to find out the difference of state-owned bank and foreign bank efficiency level in every approaches. This research shows the results that efficiency level of state-owned banks and foreign banks in Indonesia is increasing in every period between 2010-2014 using operational approach, intermediation approach and asset approach. At operational approach, the average efficiency on state-owned banks are 0,97677198 and foreign banks are 0,78301436. At intermediation approach, the average efficiency on state-owned banks are 0,98241996 and foreign banks are 0,42062963. At asset approach, the average efficiency on state-owned banks are 0,322442 and foreign banks are 0,22159316. The results of hypothesis testing shows that there is significance difference in efficiency level of atate-owned banks and foreign banks based on operational approach, intermediation approach and asset approach. Both state-owned banks and foreign banks have to increase the efficiency level on asset approach because it has the lowest values.